ANALISIS PENGARUH INVESTASI, TENAGA KERJA , TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP PERTUMBUHAN EKONOMI DI 5 NEGARA G20 TAHUN 2017 – 2022 - Jaya, Alfin Arma; Setyowati, Eni (ITB AAS Indonesia Surakarta, 2024)
The impact of information technology (IT) and telecommunications breakthroughs on a country's economy may be large. National economic progress continues, especially after the formation of the G20, a meeting of 19 leading countries and the European Union which aims to foster world collaboration. The countries included in the list include South Africa, United States, Saudi Arabia, Argentina, Australia, Brazil, India, England, Italy, Japan, Germany, Canada, South Korea, Mexico, France, Russia, China, Turkey, and the European Union. Additionally, investment and workforce levels are important factors to consider. The aim of this research is to determine the influence of investment, labor, information and communication technology on economic growth in 5 G20 countries in 2017 - 2022. This research is quantitative research. The results of this research show that using the panel data method produces the best model, namely the Common Effect Model (REM), the results of the simultaneous significant test (F test) show that in 2017-2022 the investment, labor, information and communication technology variables do not simultaneous influence on economic growth in 5 G20 countries, namely Indonesia, Korea, Brazil, Saudi Arabia, Argentina. The results of the partial significant test (t test) show that the labor variable has an influence on economic growth in 5 G20 countries. Meanwhile, two other variables, namely investment and information and communication technology, have no effect on economic growth in the 5 G20 countries, namely Indonesia, Korea, Brazil, Saudi Arabia, Argentina in 2017 - 2022. Keywords : Investment, Labor, Information and Communication Technology, Economic Growth